The Microsoft case antitrust, high technology, and consumer welfare - Page, William H. (William Hepburn), 1951-; Lopatka, John E. (Chicago, [Ill.] ; London : University of Chicago Press, 2007)
United States Department of Justice and state antitrust agencies charged that Microsoft was monopolizing market for personal computer operating systems by suppressing a competitive threat from Netscape's web browser and Sun Microsystems' Java technologies. This book examines implications of this litigation from perspective of consumer welfare.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Microsoft Corporation -- Trials, litigation, etc; Antitrust law -- United States; Restraint of trade -- United States; Computer software industry -- Law and legislation -- United States; United States -- Trials, litigation, etc; Law; United States of America, USA; Jurisprudence & general issues; Laws of specific jurisdictions & specific areas of law; Legal systems: courts & procedure; Commercial law